2020
DOI: 10.1111/head.13956
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of 3 CGRP Monoclonal Antibodies in Practice: A Retrospective Cohort Study

Abstract: Objective We sought to assess the safety and tolerability of 3 calcitonin gene‐related peptide (CGRP) monoclonal antibodies in patients with chronic migraine who have failed multiple classes of migraine preventive therapies. Background CGRP is an important neuromodulator implicated in the pathogenesis of migraine. They are approved for the treatment of episodic and chronic migraine. In current clinical practice, CGRP monoclonal antibodies are used in patients who have failed multiple preventive agents, but saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…Surprisingly, constipation was reported in maximally 3.2% of patients in the erenumab RCTs. By contrast, it is the most prevalent side effect mentioned in most real-world studies where its incidence ranges from around 8 (31,32) to more than 20% (18,19,27,29,33). The reason for the discrepancy between RCT and subsequent studies is not clear.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Surprisingly, constipation was reported in maximally 3.2% of patients in the erenumab RCTs. By contrast, it is the most prevalent side effect mentioned in most real-world studies where its incidence ranges from around 8 (31,32) to more than 20% (18,19,27,29,33). The reason for the discrepancy between RCT and subsequent studies is not clear.…”
Section: Discussionmentioning
confidence: 97%
“…A number of "real-world" studies and registries of migraine treatment with erenumab in North American (18)(19)(20)(21)(22)(23)(24)(25), European (26)(27)(28)(29)(30)(31)(32)(33), or Australian patients (34) have been published recently and included mainly patients with CM (Supplementary Table 1). With one exception (21), all the studies from North America were retrospective (18-20, 22, 23, 26), while all studies but two (26,30) studies from other geographic areas had a prospective design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the lowest rate of erenumab-associated constipation (7.6%) was found in Spanish patients ( Belvís et al, 2021 ), while the highest rates (32.6–65%) were found in Dutch ( de Vries Lentsch et al, 2021 ) and US ( Alex et al, 2020 ; Kanaan et al, 2020 ) patients as well as in a Danish cohort of patients with headache attributed to mild traumatic brain injury ( Ashina H. et al, 2020 ). A more detailed analysis indicates that constipation due to erenumab depends on dose ( Alex et al, 2020 ) and is most prominent at the start of treatment ( Lambru et al, 2020 ). Antibodies targeting CGRP itself appear to be equally liable to cause constipation as erenumab ( Table 1 ).…”
Section: Constipation As An Adverse Effect Of Calcitonin Gene-related Peptide and Calcitonin Gene-related Peptide Receptor Antibodies In mentioning
confidence: 99%
“…One of the observational studies concluded that adverse effects resulted in 33% of erenumab discontinuations [2]. Another study described 63.3% of patients as having reported an adverse effect, but they concluded that the CGRP monoclonal antibodies were well tolerated [3]. We published a study of 119 chronic migraine patients who had utilized one of the CGRP monoclonals [4].…”
mentioning
confidence: 99%